Immunomodulatory effect and Disease resistance from concoction three of Borneo plant extracts in tilapia, Oreochromis niloticus - hardi, esti handayani; Nugroho, RA; Kusuma, I W; kusuma, W; Apriza, Apriza (Aquacultura Indonesiana, 2019)
This study was conducted to evaluate the immunomodulatory activity and diseases resistance of concoction Boesenbergia pandurata/BP, Solanum ferox/SF, and Zingiber zerumbet/ZZ extract (SF, BP, and ZZ) in tilapia with the concentrations 600 mg/L BP, 900 mg/L SF and 200 mg/L ZZ against Aeromonas hydrophila and Pseudomonas fluorescens. Immunomodulatory activity was measured by testing the concoction of three plants extract to preventive and treatment pathogen infection (A. hydrophila and P. fluorescens 105colony-forming units per milliliter each bacteria). In this research, using feed administration method, the concoction of extract BP:SF:ZZ ratio was 1:1:1 and extract is given for 14 days as much as three times a day (3-5% of fish body weight). The immunomodulatory parameters (white blood cell/WBC, red blood cell/RBC, phagocytic index/IP) and relative presentation survival/RPS was observed at week 4th after challenges with bacteria through intramuscularly injection (0.1 mL/fish). The number of white blood cell (WBC) was increased significantly (P <0.05) compared to controls without extract and it also happens with red blood cell (RBC), phagocytic index also experienced a significant increasing in fish fed with combined extracts compared to controls. The results of this study indicate that giving concoction of three extracts provides the best protection (RPS) against infection of A. hydrophila and P. fluorescent. The conclusion this research is concoction of SF:BP:ZZ in the ratio of 1:1:1 have a immunomodulatory effect in tilapia and increasing protection against bacterial infections